Minimally invasive repair of right-sided blunt traumatic diaphragmatic injury. Issue 11 (4th November 2020) - Shichiri, Keiko; Imamura, Kiyotaka; Takada, Minoru; Anbo, Yoshiyasu
Abstract : Right-sided blunt traumatic diaphragmatic injury (TDI) is a rare injury that is rarely repaired by the minimally invasive approach in the acute setting. Laparoscopic repair of right-sided TDI is challenging because the liver often obstructs access to the injury site. Herein, we report a case wherein acute right-sided blunt TDI was successfully repaired using a combined laparoscopic and thoracoscopic approach. A 30-year-old man presented with shortness of breath after falling on his back while jumping on a snowboard. CT revealed a right-sided TDI. As the patient was haemodynamically stable, laparoscopic repair was planned. Laparoscopy revealed a right-sided diaphragmatic rupture. As the posterior portion was covered by the liver and difficult to access, we added trocars in the chest cavity and closed the diaphragmatic defect with a thoracic approach. A combined laparoscopic and thoracoscopic approach can repair right-sided diaphragmatic injury by a minimally invasive approach even in the acute setting.